Lack of association between nutritional status and change in clinical category among HIV-infected children in Brazil - Centeville, Maraisa; Morcillo, André Moreno; Barros Filho, Antonio de Azevedo; Silva, Marcos Tadeu Nolasco da; Toro, Adyléia Aparecida Dalbo Contrera; Vilela, Maria Marluce dos Santos (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Malnutrition is com- mon among HIV-infected children. Our objective was to study the occurrence of malnutrition and its relationship with changes in clinical category among HIV-infected children. DESIGN AND SETTING: Longitudinal study, at the Pediatrics Department and Pediatrics Inves- tigation Center (CIPED), Faculdade de Ciências Médicas da Universidade Estadual de Campinas (Unicamp). METHODS: We reviewed the hospital records of 127 vertically HIV-infected children. Anthropo- metric measurements were obtained at the begin- ning of follow-up, at clinical category change and ﬁve months later. These were converted to z-scores of weight/age, height/age and weight/ height. Data were presented as means, standard deviations, frequency counts and percentages. The Wilcoxon and Kruskal-Wallis tests and odds ratios were used in the analysis. RESULTS: We found that 51 (40.2%) were undernourished and 40 (31.5%) were stunted, with higher risk of being included in clinical category C. There was an association between nutritional condition and the clinical categories of the Centers for Disease Control classiﬁcation (1994), and with age at symptom onset (except for height z-score). During follow-up, 36 patients (28.4%) changed their clinical category, which occurred early among the undernourished patients. The group that changed its clinical category maintained the same z-score distribution for weight, height and weight/height throughout follow-up. CONCLUSION: Aids manifestation severity was associated with nutritional status and with age at symptom onset, but change in clinical category was not followed by worsening of nutritional status.